A high cross-linking efficiency xlpe insulating material power cable and a preparation method thereof

CN122843015APending Publication Date: 2026-09-29ZHEJIANG HONGCE CABLE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610725843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-25
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0004]该类方案能够满足常规电缆绝缘料的制备需要,但交联剂、助交联剂多采用常规混合或普通后加入方式,助交联剂与聚乙烯反应链段之间的预分散状态受混合过程影响较大;若提高过氧化物用量或延长硫化时间以保证交联程度,可能带来加工窗口变窄、残留副产物增加及热延伸控制难度增大的问题

Benefits of technology

[0044]本发明以端基乙烯基富集低密度聚乙烯作为助交联母粒的主体材料,将反应型助交联剂与第一部分复合抗氧剂在90~115℃下熔融分散,随后在60~80℃、惰性气氛和负压条件下分2~4次加入复合有机过氧化物,制得交联效率母粒,再与电缆级低密度聚乙烯稀释树脂、第二部分复合抗氧剂和防焦调节剂在不高于105℃下低剪切混合。该分阶段制备方式使助交联剂预混、过氧化物加入和主体树脂稀释混合分别在较低风险温度区间内完成,有利于减少直接混合中局部浓度偏高和挤出前提前交联的风险;所得绝缘料经三层共挤和连续硫化后,可形成具有稳定凝胶含量、热延伸性能、机械性能和电绝缘性能的XLPE绝缘层,并降低脱气后过氧化物残留量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122843015A_ABST
    Figure CN122843015A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of high-performance cable technology, specifically relating to a high-crosslinking-efficiency XLPE insulated power cable and its preparation method. The cable includes a conductor and, sequentially, a conductor shielding layer, an XLPE insulation layer, an insulating shielding layer, a metal shielding layer, and an outer sheath covering the outside of the conductor. The XLPE insulation layer is formed by three-layer co-extrusion and continuous vulcanization crosslinking of high-crosslinking-efficiency XLPE insulation material. The insulation material includes cable-grade low-density polyethylene diluted resin, end-group vinyl-enriched low-density polyethylene, a reactive crosslinking aid, a composite organic peroxide, a composite antioxidant, and a scorch prevention regulator. During preparation, crosslinking masterbatch is first prepared, then crosslinking efficiency masterbatch is prepared, and finally, the insulation material is obtained through low-shear mixing. The cable prepared by this invention exhibits more stable thermal elongation, mechanical properties, and electrical insulation properties of its insulation layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of high-performance power cables and cross-linked polyethylene insulation materials, specifically relating to a high cross-linking efficiency XLPE insulation power cable and its preparation method. Background Technology

[0002] Cross-linked polyethylene (XLPE) is widely used in the insulation layers of medium-voltage, high-voltage, and ultra-high-voltage power cables due to its good electrical insulation, heat resistance, and mechanical properties. Existing peroxide-crosslinked polyethylene insulation materials typically use low-density polyethylene as a matrix, adding peroxide crosslinking agents, co-crosslinking agents, and antioxidants, and then forming an XLPE insulation layer through mixing, granulation, three-layer co-extrusion, and continuous vulcanization.

[0003] Chinese patent CN115819872A discloses a peroxide crosslinked polyethylene cable material for insulation, which includes 100 parts of low-density polyethylene resin, 1.6 to 2.0 parts of crosslinking agent, 0.1 to 0.3 parts of co-crosslinking agent, 0.01 to 0.03 parts of high-melting-point antioxidant and 0.005 to 0.01 parts of low-melting-point antioxidant, wherein the co-crosslinking agent can be TAIC or TMPTMA, and the crosslinking agent is a peroxide compound.

[0004] This type of solution can meet the preparation requirements of conventional cable insulation materials, but the crosslinking agents and co-crosslinking agents are mostly added in a conventional mixing or post-addition manner. The pre-dispersion state between the co-crosslinking agent and the polyethylene reaction chain segments is greatly affected by the mixing process. If the amount of peroxide is increased or the vulcanization time is extended to ensure the degree of crosslinking, it may lead to problems such as a narrowing of the processing window, an increase in residual by-products, and increased difficulty in controlling thermal elongation. Therefore, it is necessary to provide an XLPE insulation power cable and its preparation method that regulates the crosslinking system through masterbatch and staged addition. Summary of the Invention

[0005] This invention aims to provide a high-crosslinking-efficiency XLPE insulation power cable and its preparation method. By combining a process of enriching low-density polyethylene carriers with end-group vinyl groups, premixing reactive crosslinking agents, and adding composite organic peroxides in batches under low-temperature negative pressure, the stability of the peroxide crosslinking system in the insulation material is improved. This reduces the risk of local high crosslinking agent concentration and premature crosslinking caused by direct mixing, and enables the insulation layer to have stable gel content, thermal elongation properties, and electrical insulation properties after continuous vulcanization.

[0006] To achieve the above-mentioned technical objectives, the present invention provides the following technical solution.

[0007] In a first aspect, the present invention provides a high cross-linking efficiency XLPE insulated power cable, comprising a conductor and a conductor shielding layer, an XLPE insulation layer, an insulation shielding layer, a metal shielding layer and an outer sheath covering the outside of the conductor;

[0008] The XLPE insulation layer is formed by three-layer co-extrusion and continuous vulcanization cross-linking of high cross-linking efficiency XLPE insulation material;

[0009] The raw material system for preparing the high crosslinking efficiency XLPE insulation material includes cable-grade low-density polyethylene diluted resin, end-group vinyl-enriched low-density polyethylene, reactive crosslinking agent, composite organic peroxide, composite antioxidant, and scorch prevention modifier;

[0010] The preparation process of the high crosslinking efficiency XLPE insulation material includes the following steps:

[0011] T1. End-group vinyl-enriched low-density polyethylene, reactive co-crosslinking agent and first part of composite antioxidant are added to a closed mixing equipment and melt-dispersed at 90-115°C to obtain co-crosslinking masterbatch.

[0012] T2. Cool the crosslinking aid masterbatch to 60-80°C, and add the composite organic peroxide in 2-4 portions under an inert atmosphere and a negative pressure of -0.03 to -0.08 MPa. Stir for 5-20 minutes after each addition under the negative pressure before adding the next portion to obtain the crosslinking efficiency masterbatch.

[0013] T3. The crosslinking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C to obtain the high crosslinking efficiency XLPE insulation material.

[0014] Preferably, based on 100 parts of the combined amount of the cable-grade low-density polyethylene diluted resin and the end-group vinyl-enriched low-density polyethylene, the high crosslinking efficiency XLPE insulation material comprises the following components:

[0015] 75-88 parts of cable-grade low-density polyethylene diluted resin; 12-25 parts of end-vinyl-enriched low-density polyethylene;

[0016] 1.05–1.55 parts of composite organic peroxide; 0.10–0.28 parts of reactive crosslinking agent; 0.06–0.18 parts of composite antioxidant; 0.05–0.18 parts of scorch prevention regulator.

[0017] Preferably, the end-terminated vinyl-enriched low-density polyethylene has an end-terminated vinyl index of 0.45–0.85, an end-terminated vinyl content of 0.35–1.20 ions / 10000C, a density of 0.918–0.925 g / cm³, a melt flow rate of 1.5–3.0 g / 10 min, a total metal ion impurity content of no more than 5 ppm, and an ash content of no more than 50 ppm.

[0018] Preferably, the reactive co-crosslinking agent comprises triallyl isocyanurate and trimethylolpropane trimethacrylate, with a mass ratio of 1:0.20 to 0.80.

[0019] In step T1, the reactive crosslinking agent is added to the closed mixing equipment in 2 to 3 portions, and after each addition, it is melt-dispersed at 90 to 115°C for 3 to 8 minutes.

[0020] The first part of the composite antioxidant is added after the end-group vinyl-enriched low-density polyethylene begins to melt, and is added before the first addition of the reactive co-crosslinking agent.

[0021] Preferably, the composite organic peroxide includes dicumyl peroxide, bis-tert-butylperoxyisopropylbenzene, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane.

[0022] The mass ratio of dicumyl peroxide to bis-tert-butylperoxide is 1:0.35 to 0.85.

[0023] 2,5-Dimethyl-2,5-di-tert-butylperoxyhexane accounts for 5-20% of the total amount of complex organic peroxides.

[0024] Preferably, when preparing the crosslinking aid masterbatch, the rotation speed of the closed mixing equipment is 30-80 rpm, and the melt dispersion time is 8-25 min;

[0025] After the crosslinking masterbatch is cooled to 60-80°C, it is first purged under an inert atmosphere for 3-10 minutes before adding the composite organic peroxide, and then the pressure is reduced to -0.03 to -0.08 MPa.

[0026] When the composite organic peroxide is added in 2 to 4 portions, the temperature fluctuation between two adjacent additions shall not exceed 5°C.

[0027] Preferably, the crosslinking efficiency masterbatch has a particle size of 0.5–3.0 mm;

[0028] When the crosslinking efficiency masterbatch is mixed with cable-grade low-density polyethylene diluted resin under low shear, the mixing temperature is 85-105℃, the rotation speed of the mixing equipment is 20-60rpm, and the mixing time is 5-20min.

[0029] After low-shear mixing, the material is extruded, granulated, cooled at low temperature, and sieved to obtain high cross-linking efficiency XLPE insulation particles. The outlet temperature of the low-temperature air cooling is 15-30℃, and the sieving process retains particles with a particle size of 2-5mm.

[0030] Preferably, the composite antioxidant is composed of a hindered phenolic antioxidant with a melting point of not less than 120°C and a thioester or phosphite auxiliary antioxidant with a melting point of less than 115°C, with a mass ratio of 1:0.25 to 0.70.

[0031] The scorching inhibitor is α-methylstyrene dimer, p-benzoquinone scorching inhibitor, or a combination thereof;

[0032] The XLPE insulation layer, after degassing, has a gel content of not less than 82%, a thermal elongation of not more than 60% under conditions of 200℃ and 0.2MPa, and a residual content of composite organic peroxide not more than 0.18%.

[0033] Secondly, the present invention also provides a method for preparing the power cable described in the first aspect, comprising the following steps:

[0034] S1. Weigh out the following according to the formula: end-group vinyl enriched low-density polyethylene, reactive crosslinking agent, composite organic peroxide, composite antioxidant, anti-scorching agent and cable-grade low-density polyethylene diluted resin.

[0035] S2. End-group vinyl-enriched low-density polyethylene, reactive crosslinking agent and first part of composite antioxidant are added to a closed mixing equipment and melt-mixed in a closed environment at 90-115°C to obtain crosslinking masterbatch.

[0036] S3. Cool the crosslinking aid masterbatch to 60-80°C, and add the composite organic peroxide in 2-4 portions under an inert atmosphere and a negative pressure of -0.03 to -0.08 MPa. Stir for 5-20 minutes after each addition under the negative pressure to obtain the crosslinking efficiency masterbatch.

[0037] S4. The cross-linking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C and granulated to obtain high cross-linking efficiency XLPE insulation material.

[0038] S5. The conductor shielding material, high cross-linking efficiency XLPE insulation material and insulation shielding material are co-extruded onto the outside of the conductor through a three-layer co-extrusion die head to form a conductor shielding layer, a cross-linking insulation layer and an insulation shielding layer.

[0039] S6. The co-extruded cable core is fed into a continuous vulcanization pipeline to cross-link the insulation layer to be cross-linked to form an XLPE insulation layer.

[0040] S7. Cool, degas, wrap with a metal shielding layer, and extrude an outer sheath to obtain the high cross-linking efficiency XLPE insulation power cable.

[0041] Preferably, in step S6, the continuous vulcanization pipe is provided with a preheating section, a main cross-linking section and a post-cross-linking section in sequence along the direction of travel of the co-extruded cable core;

[0042] The temperature of the preheating section is 145–165°C, the temperature of the main cross-linking section is 180–205°C, and the temperature of the post-cross-linking section is 205–225°C.

[0043] Preferably, in step S7, the degassing is carried out at 60–80°C for 48–96 hours.

[0044] This invention uses vinyl-enriched low-density polyethylene (LDPE) as the main material for the crosslinking aid masterbatch. A reactive crosslinking aid and a first-part composite antioxidant are melt-dispersed at 90–115°C. Subsequently, a composite organic peroxide is added in 2–4 stages at 60–80°C under an inert atmosphere and negative pressure to obtain the crosslinking efficiency masterbatch. This masterbatch is then mixed with cable-grade LDPE diluted resin, a second-part composite antioxidant, and an anti-scorching regulator at a low-shear temperature not exceeding 105°C. This staged preparation method allows the premixing of the crosslinking aid, the addition of the peroxide, and the dilution and mixing of the main resin to be completed within a lower-risk temperature range, which helps reduce the risk of locally high concentrations during direct mixing and premature crosslinking before extrusion. After three-layer co-extrusion and continuous vulcanization, the resulting insulation material forms an XLPE insulation layer with stable gel content, thermal elongation, mechanical properties, and electrical insulation properties, while reducing the residual peroxide content after degassing. Attached Figure Description

[0045] Figure 1 This is a schematic diagram of the layered structure of the high cross-linking efficiency XLPE insulation material power cable of the present invention.

[0046] Figure 2 This is a schematic diagram illustrating the preparation process of the high crosslinking efficiency XLPE insulation material and its power cable according to the present invention.

[0047] The components are: 1. Conductor; 2. Conductor shielding layer; 3. XLPE insulation layer; 4. Insulation shielding layer; 5. Metal shielding layer; 6. Outer sheath. Detailed Implementation

[0048] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present invention.

[0049] This invention provides a high-crosslinking-efficiency XLPE insulating power cable and its preparation method. For example... Figure 1As shown, the power cable includes a conductor 1 and a conductor shielding layer 2, an XLPE insulation layer 3, an insulation shielding layer 4, a metal shielding layer 5, and an outer sheath 6 covering the outside of the conductor 1. The conductor shielding layer 2, the XLPE insulation layer 3, and the insulation shielding layer 4 can be formed by a three-layer co-extrusion process. The XLPE insulation layer 3 is formed by continuous vulcanization crosslinking of high crosslinking efficiency XLPE insulation material.

[0050] like Figure 2 As shown, the high crosslinking efficiency XLPE insulation material is prepared using a staged batching method, including the preparation of crosslinking aid masterbatch, crosslinking efficiency masterbatch, and low-shear mixing with cable-grade low-density polyethylene diluted resin. After forming the insulation layer to be crosslinked, it is further processed into a cable through three-layer co-extrusion, continuous vulcanization, and post-treatment. This staged batching method ensures that the premixing of the crosslinking aid, the addition of the peroxide, and the mixing of the main resin are completed in their respective process stages. The specific implementation method will be explained below in conjunction with the raw material composition, process parameters, examples, and test data.

[0051] I. Raw Material Description

[0052] In this embodiment, the cable-grade low-density polyethylene (LDPE) diluent resin is a LDPE resin suitable for power cable insulation layers. Its density can be 0.918–0.925 g / cm³, its melt flow rate can be 1.5–3.0 g / 10 min, its ash content can be no higher than 50 ppm, and its total metal ion impurities can be no higher than 5 ppm. The cable-grade LDPE diluent resin is mainly used to form the main polyethylene phase of the XLPE insulation layer 3 and to ensure the basic processing performance of the insulation material during extrusion and continuous vulcanization.

[0053] End-terminated vinyl-enriched low-density polyethylene (LDPE) is a type of polyethylene resin with high reactivity. Its end-terminated vinyl index can be 0.45–0.85, end-terminated vinyl content can be 0.35–1.20 ions / 10000C, density can be 0.918–0.925 g / cm³, melt flow rate can be 1.5–3.0 g / 10 min, total metal ion impurities can be no higher than 5 ppm, and ash content can be no higher than 50 ppm. The end-terminated vinyl index can be calculated by measuring the integral ratio of end-terminated vinyl groups, endolactone groups, and divinyl groups using 1H NMR spectroscopy.

[0054] The reactive co-crosslinking agent includes triallyl isocyanurate and trimethylolpropane trimethacrylate, with a mass ratio of 1:0.20 to 0.80. During the preparation of the co-crosslinking masterbatch, the reactive co-crosslinking agent can be added in 2 to 3 portions to a closed mixing apparatus. After each addition, it should be melt-dispersed at 90 to 115°C for 3 to 8 minutes to improve the dispersion of the co-crosslinking agent in low-density polyethylene enriched with end-group vinyl groups.

[0055] The composite organic peroxide includes dicumyl peroxide, di-tert-butylperoxypropylbenzene, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. The mass ratio of dicumyl peroxide to di-tert-butylperoxypropylbenzene can be 1:0.35–0.85, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane accounts for 5–20% of the total composite organic peroxide. The composite organic peroxide is used to decompose and generate free radicals during continuous vulcanization and to form a cross-linked structure in the polyethylene system.

[0056] The composite antioxidant consists of a hindered phenolic antioxidant and a thioester or phosphite auxiliary antioxidant. The hindered phenolic antioxidant has a melting point not lower than 120℃, and the auxiliary antioxidant has a melting point lower than 115℃; their mass ratio can be 1:0.25–0.70. The hindered phenolic antioxidant can be pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the auxiliary antioxidant can be distearate thiodipropionate or tris(2,4-di-tert-butylphenyl)phosphite. The composite antioxidant is divided into a first part and a second part. The first part is used in the preparation stage of the crosslinking masterbatch, and the second part is used in the preparation stage of high crosslinking efficiency XLPE insulation material.

[0057] Anti-scorching modifiers can be α-methylstyrene dimer, p-benzoquinone anti-scorching agents, or combinations thereof, used to adjust the processing stability of insulating materials during mixing, granulation, and extrusion stages.

[0058] II. Cable Structure

[0059] like Figure 1 As shown, conductor 1 can be a copper conductor or an aluminum conductor, specifically a round, tightly stranded conductor, a split conductor, or other conductor structures suitable for power cables. A conductor shielding layer 2 is provided on the outside of conductor 1, which can be made of semi-conductive polyolefin shielding material. An XLPE insulation layer 3 is provided on the outside of conductor shielding layer 2, formed by three-layer co-extrusion and continuous vulcanization of the high cross-linking efficiency XLPE insulation material of this invention. An insulating shielding layer 4 is provided on the outside of XLPE insulation layer 3, which can be made of semi-conductive insulating shielding material. A metal shielding layer 5 is provided on the outside of insulating shielding layer 4, which can be a copper tape wrapping layer, a copper wire shielding layer, an aluminum-plastic composite tape shielding layer, or a combination thereof. An outer sheath 6 is provided on the outside of metal shielding layer 5, which can be made of polyethylene sheathing material, polyvinyl chloride sheathing material, or low-smoke halogen-free sheathing material.

[0060] During cable manufacturing, the conductor shielding layer 2, the cross-linked insulation layer, and the insulating shielding layer 4 are preferably formed simultaneously using a three-layer co-extrusion method. Three-layer co-extrusion reduces interlayer contamination and interface defects, and creates a stable contact interface between the cross-linked insulation layer and the shielding layers on both sides. After co-extrusion, the cable core enters a continuous vulcanization pipeline and undergoes preheating, main cross-linking, and post-cross-linking treatments, causing the cross-linked insulation layer to form the XLPE insulation layer 3.

[0061] III. Preparation of High Crosslinking Efficiency XLPE Insulation Material

[0062] like Figure 2 As shown, high crosslinking efficiency XLPE insulation material can be prepared according to the following steps.

[0063] 1. Preparation of cross-linking masterbatch

[0064] Low-density polyethylene enriched with end- group vinyl groups, a reactive crosslinking agent, and a first-part composite antioxidant are added to a closed mixing apparatus and melt-dispersed at 90–115°C to obtain crosslinking masterbatch. The closed mixing apparatus can be an internal mixer, a closed twin-screw mixer, or a low-speed mixing apparatus with temperature control and exhaust ports.

[0065] In one embodiment, end-vinyl-enriched low-density polyethylene is first added to a closed mixing apparatus to soften and melt at 90–115°C. After the end-vinyl-enriched low-density polyethylene begins to melt, the first portion of the composite antioxidant is added, completing the addition before the first addition of the reactive co-crosslinking agent. Subsequently, the reactive co-crosslinking agent is added in 2–3 portions, with continued melting and dispersion for 3–8 minutes after each addition. The rotation speed of the closed mixing apparatus can be 30–80 rpm, and the total melting and dispersion time can be 8–25 minutes. After mixing, the material is cooled and pelletized to obtain co-crosslinking masterbatch.

[0066] 2. Preparation of cross-linking efficiency masterbatch

[0067] Add the crosslinking aid masterbatch to a sealed device equipped with an inert gas inlet and a negative pressure interface, and first purge with an inert atmosphere for 3 to 10 minutes. The inert atmosphere can be nitrogen or argon. Then, cool or keep the crosslinking aid masterbatch at 60 to 80°C, and evacuate to a gauge pressure of -0.03 to -0.08 MPa.

[0068] Under the above conditions, the composite organic peroxide is added in 2 to 4 batches. After each addition, the mixture is stirred for 5 to 20 minutes under the negative pressure condition before the next addition. When adding the composite organic peroxide in batches, the temperature fluctuation between two adjacent additions should preferably not exceed 5°C. The composite organic peroxide can be added through a closed feeding valve, a metering pump, or a peristaltic pump. After the composite organic peroxide is added, stirring continues for 5 to 15 minutes under an inert atmosphere, followed by cooling and discharge to obtain crosslinking efficiency masterbatch.

[0069] In this step, the temperature of the crosslinking aid masterbatch is controlled at 60–80°C, which is lower than the main crosslinking temperature range of conventional continuous vulcanization. This helps reduce the risk of premature decomposition of the composite organic peroxide during the masterbatch preparation stage. The negative pressure condition and the batch addition method help ensure sufficient contact between the composite organic peroxide and the crosslinking aid masterbatch, and reduce the localized high concentration when added all at once.

[0070] 3. Preparation of high cross-linking efficiency XLPE insulation material

[0071] The cross-linking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C to obtain a high cross-linking efficiency XLPE insulation material.

[0072] In one embodiment, the mixing temperature is 85–105°C, the mixing equipment speed is 20–60 rpm, and the mixing time is 5–20 min. After low-shear mixing, the mixture is extruded, granulated, cooled at low temperature, and sieved to obtain high-crosslinking-efficiency XLPE insulation particles. The outlet air temperature of the low-temperature air cooler is 15–30°C, and the sieving process retains particles with a diameter of 2–5 mm. The granulated insulation particles should be sealed and stored to avoid moisture and prolonged exposure to high temperatures.

[0073] IV. Manufacturing Methods of Power Cables

[0074] The high cross-linking efficiency XLPE insulation power cable of the present invention can be prepared according to the following steps.

[0075] S1. Weigh out the following according to the formula: end-group vinyl enriched low-density polyethylene, reactive crosslinking agent, composite organic peroxide, composite antioxidant, scorch prevention regulator and cable-grade low-density polyethylene diluted resin.

[0076] S2. End-group vinyl-enriched low-density polyethylene, reactive crosslinking agent and first part of composite antioxidant are added to a closed mixing equipment and melt-mixed in a closed environment at 90-115°C to obtain crosslinking masterbatch.

[0077] S3. Cool the crosslinking aid masterbatch to 60-80°C, and add the composite organic peroxide in 2-4 portions under an inert atmosphere and a negative pressure of -0.03 to -0.08 MPa. Stir for 5-20 minutes after each addition under the negative pressure to obtain the crosslinking efficiency masterbatch.

[0078] S4. The cross-linking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C and granulated to obtain high cross-linking efficiency XLPE insulation material.

[0079] S5. The conductor shielding material, high cross-linking efficiency XLPE insulation material, and insulation shielding material are co-extruded onto the outside of conductor 1 through a three-layer co-extrusion die head to form conductor shielding layer 2, cross-linking insulation layer, and insulation shielding layer 4. The temperature of each zone of the extruder can be set according to the equipment and linear speed. The temperature of the insulation material extrusion section is preferably controlled at 105-125℃, and the die head temperature is preferably controlled at 115-130℃.

[0080] S6. The co-extruded cable core is fed into a continuous vulcanization pipeline to cross-link the insulation layer to form XLPE insulation layer 3. The continuous vulcanization pipeline is sequentially configured with a preheating section, a main cross-linking section, and a post-cross-linking section along the direction of travel of the co-extruded cable core. The temperature of the preheating section is 145–165℃, the temperature of the main cross-linking section is 180–205℃, and the temperature of the post-cross-linking section is 205–225℃. A nitrogen pressure environment can be used inside the continuous vulcanization pipeline; the nitrogen pressure can be set according to the cable specifications and insulation layer thickness.

[0081] S7. The cross-linked cable core is cooled, degassed, wrapped with a metal shielding layer 5, and extruded with an outer sheath 6 to obtain a high-cross-linking-efficiency XLPE insulated power cable. Degasing can be carried out at 60-80℃ for 48-96 hours.

[0082] V. Testing Methods

[0083] To illustrate the technical solution of the present invention, the insulating materials and cable insulation layers obtained in the embodiments and comparative examples were tested as follows. Unless otherwise specified, each test sample was taken from the degassed XLPE insulation layer 3, and the samples were placed in an environment of 23°C and 50% relative humidity for no less than 24 hours before sampling. At least 3 parallel samples were tested for each group of samples, and the average value of the results was taken.

[0084] 1. Crosslinking characteristic test

[0085] The crosslinking characteristics of the insulation material were tested using a rotorless vulcanizer or a torque rheometer. Uncrosslinked, high-crosslinking-efficiency XLPE insulation material granules were pressed into sheets as test samples, with a sample mass of 4–6 g. The test temperature was 180℃, the test time was 30 min, the oscillation frequency was 1.67 Hz, and the amplitude was ±0.5°. During the test, the minimum torque M_L, the maximum torque M_H, and the time t_{90} required to reach 90% crosslinking torque were recorded. The crosslinking efficiency index η_c was calculated using the following formula:

[0086]

[0087] In the formula, Crosslinking efficiency index; This is the highest torque; Minimum torque; This refers to the dosage of compound organic peroxides; Time required to achieve 90% cross-linking torque.

[0088] 2. Gel content test

[0089] The gel content of the cross-linked XLPE insulation layer 3 was determined using xylene extraction. Samples were cut along the thickness direction of the XLPE insulation layer 3. After removing the conductor shielding layer 2 and the insulating shielding layer 4, the XLPE insulation layer 3 was cut into small pieces no larger than 1 mm × 1 mm. Approximately 0.3 g of sample was weighed and recorded as the pre-extraction mass. The sample was placed in a 120-mesh stainless steel mesh bag and then placed in a Soxhlet extractor containing xylene. Extraction was performed for 8 hours under xylene reflux. After extraction, the mesh bag was removed, and the sample was rinsed twice with fresh xylene, and then once with anhydrous ethanol.

[0090] After rinsing, the sample was placed in an 80℃ vacuum drying oven for 4 hours, then transferred to a desiccator to cool to room temperature and weighed. The drying and weighing were repeated until the difference between two consecutive weighings was no more than 0.5 mg. The final mass was recorded as the mass of the insoluble matter after extraction and drying. The gel content G is calculated using the following formula:

[0091]

[0092] In the formula, G represents the gel content; To ensure the quality of the samples before sampling; This refers to the mass of the insoluble matter after extraction and drying.

[0093] 3. Thermal extension test

[0094] The thermal elongation and permanent deformation after cooling of the XLPE insulation layer 3 were tested according to the thermal elongation test method for cable insulation materials. The degassed XLPE insulation layer 3 was prepared into dumbbell-shaped specimens with a thickness of 0.8–2.0 mm and a width of 4 mm for the parallel section in the middle of the specimen. The marking spacing was as follows. The diameter is 20 mm. Each test group should have no fewer than 3 samples.

[0095] During testing, the specimen was vertically suspended in a 200℃ thermal elongation test chamber, and a load equivalent to 0.2 MPa stress was applied to the lower end of the specimen. After the specimen was subjected to the load at 200℃ for 15 minutes, the length of the mark under the load was measured. The thermal elongation H was calculated. The load was then removed while the specimen was suspended, allowing it to recover at 200°C for 5 minutes. After cooling to room temperature, the length of the mark after cooling was measured. And calculate the permanent deformation P after cooling.

[0096] The thermal elongation H is calculated using the following formula:

[0097]

[0098] The permanent deformation P after cooling is calculated using the following formula:

[0099]

[0100] In the formula, H is the thermal elongation; P is the permanent deformation after cooling. This is the initial marking length; The length of the marking after the load is applied; This is the length of the marking after cooling.

[0101] 4. Test for residual content of compound organic peroxides

[0102] The residual amount of complex organic peroxides in the degassed XLPE insulation layer 3 was determined by gas chromatography with external standard method. Sampling was performed in the middle region along the thickness direction of the XLPE insulation layer 3. After removing approximately 0.2 mm of material from both the inner and outer surfaces, the sample was cut into small pieces with a particle size no larger than 1 mm. 1.000 g of sample was weighed and placed in a 20 mL headspace vial or a sealed extraction bottle. 10.0 mL of chromatographically pure n-hexane was added as the extraction solvent. The bottle was sealed and extracted in a 60 °C water bath for 2 h, with shaking every 30 min during extraction. After extraction, the sample was cooled to room temperature, and the supernatant was filtered through a 0.22 μm organic filter membrane before analysis.

[0103] The gas chromatography conditions were as follows: a non-polar capillary column with a length of 30 m, an inner diameter of 0.25 mm, and a film thickness of 0.25 μm was used; the carrier gas was high-purity nitrogen or helium; the injection port temperature was 250 °C; the detector was a flame ionization detector with a detector temperature of 280 °C; the injection volume was 1 μL; and the split ratio was 20:1. The temperature program was as follows: an initial temperature of 80 °C held for 2 min, then increased to 260 °C at a rate of 10 °C / min and held for 8 min.

[0104] External standard solutions were prepared using standards of dicumyl peroxide, di-tert-butylperoxypropylbenzene, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. Mixed standard solutions of 0.01 mg / mL, 0.05 mg / mL, 0.10 mg / mL, 0.20 mg / mL, and 0.50 mg / mL were prepared using n-hexane as solvent. These solutions were injected separately, and standard curves were established to correlate peak area with concentration. The correlation coefficient of the standard curves was not less than 0.995. The corresponding concentrations were calculated based on the peak areas of each component in the sample extract, and the residual amount of the complex organic peroxide was calculated according to the sample mass and extraction volume. The residual amount R of the complex organic peroxide was calculated using the following formula:

[0105]

[0106] In the formula, R represents the residual amount of composite organic peroxide; is the mass concentration of the i-th organic peroxide in the extract; V is the volume of the extract. The mass is the sample mass; i represents dicumyl peroxide, bis-tert-butylperoxyisopropylbenzene, or 2,5-dimethyl-2,5-di-tert-butylperoxyhexane.

[0107] 5. Electrical performance testing

[0108] The power frequency breakdown strength was tested according to the power frequency breakdown test method for solid insulating materials. The degassed XLPE insulation layer 3 was hot-pressed into sheet specimens with a thickness of 1.0 mm ± 0.1 mm. The specimen surface should be flat, free of bubbles and visible impurities. Symmetrical cylindrical electrodes with rounded edges were used as the test electrodes. The test medium was air or insulating oil, and all samples were tested under the same medium conditions. A continuous and uniform voltage increase was used at a rate of 1 kV / s. The breakdown voltage was recorded and converted to power frequency breakdown strength according to the specimen thickness. Each group of samples contained at least five parallel specimens, and the average value was taken.

[0109] Volume resistivity was determined according to the test method for volume resistivity of solid insulating materials. The sample was conditioned for 24 hours at 23℃ and 50% relative humidity before testing. The test voltage was 500V or 1000V, the electrolysis time was 60s, the steady-state current was recorded, and the volume resistivity was calculated. Dielectric loss factor was tested at 50Hz, with a sample thickness of 1.0mm ± 0.1mm and a test temperature of 23℃.

[0110] 6. Mechanical performance testing

[0111] The cross-linked and degassed XLPE insulation layer 3 was prepared into standard dumbbell specimens with a thickness of 0.8–2.0 mm. Before testing, the specimens were placed in an environment of 23℃ and 50% relative humidity for at least 24 hours. Tensile strength and elongation at break were tested using an electronic universal testing machine at a tensile speed of 250 mm / min. The clamp spacing was set according to the specimen specifications. Five parallel specimens were tested for each group of samples, and the average value was taken.

[0112] VI. Examples

[0113] 1. Example 1

[0114] This embodiment describes the preparation of a high-crosslinking-efficiency XLPE insulation material for power cables. Based on a total volume of 100 parts of cable-grade low-density polyethylene diluted resin and end-group vinyl-enriched low-density polyethylene, the insulation material formulation is as follows: 83 parts cable-grade low-density polyethylene diluted resin, 17 parts end-group vinyl-enriched low-density polyethylene, 1.30 parts composite organic peroxide, 0.18 parts reactive crosslinking agent, 0.12 parts composite antioxidant, and 0.10 parts anti-scorching modifier.

[0115] The end-vinyl index of the vinyl-enriched low-density polyethylene is 0.66, the end-vinyl content is 0.72 ions / 10000C, the density is 0.922 g / cm³, the melt mass flow rate is 2.1 g / 10 min, the total metal ion impurities are 3.2 ppm, and the ash content is 32 ppm.

[0116] The reactive co-crosslinking agent consists of triallyl isocyanurate and trimethylolpropane trimethacrylate in a mass ratio of 1:0.45. The composite organic peroxide consists of dicumyl peroxide, di-tert-butylperoxyisopropylbenzene, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, with a mass ratio of dicumyl peroxide to di-tert-butylperoxyisopropylbenzene of 1:0.55, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane accounting for 10% of the total composite organic peroxide. The composite antioxidant consists of hindered phenolic antioxidants and thioester auxiliary antioxidants in a mass ratio of 1:0.45. The scorch prevention regulator uses α-methylstyrene dimer.

[0117] In preparation, end-group vinyl-enriched low-density polyethylene, a reactive co-crosslinking agent, and a first-part composite antioxidant are added to a closed mixing apparatus and melt-dispersed at 105°C for 15 minutes at a rotation speed of 50 rpm to obtain the co-crosslinking masterbatch. The reactive co-crosslinking agent is added in two portions, with each addition followed by 5 minutes of melt-dispersion.

[0118] The crosslinking aid masterbatch was cooled to 70°C, purged with nitrogen for 5 minutes, and then evacuated to a negative pressure of -0.06 MPa. The composite organic peroxide was added in three portions, and stirred for 10 minutes under the same negative pressure after each addition to obtain the crosslinking efficiency masterbatch.

[0119] The cross-linking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant, and the anti-scorching modifier were mixed at 95°C for 12 minutes under low shear at a speed of 40 rpm. After low shear mixing, the mixture was extruded, granulated, cooled at 20°C, and sieved to obtain high cross-linking efficiency XLPE insulation particles with a particle size of 2–5 mm.

[0120] The cable insulation structure was prepared using a three-layer co-extrusion process. The preheating temperature of the continuous vulcanization pipeline was 155℃, the main cross-linking temperature was 192℃, and the post-cross-linking temperature was 215℃. After cross-linking, the cable core was degassed at 70℃ for 72 hours, and then a metal shielding layer 5 and an outer sheath 6 were added to obtain the power cable sample.

[0121] 2. Example 2

[0122] This embodiment is basically the same as Embodiment 1, except that, based on a total volume of 100 parts of cable-grade low-density polyethylene diluted resin and end-group vinyl-enriched low-density polyethylene, the total volume is 88 parts of cable-grade low-density polyethylene diluted resin, 12 parts of end-group vinyl-enriched low-density polyethylene, 1.05 parts of composite organic peroxide, 0.10 parts of reactive crosslinking agent, 0.06 parts of composite antioxidant, and 0.05 parts of anti-scorching regulator.

[0123] The end-vinyl index of the vinyl-enriched low-density polyethylene was 0.48, the end-vinyl content was 0.40 per 10000°C, the density was 0.921 g / cm³, and the melt flow rate was 2.4 g / 10 min.

[0124] In the reactive co-crosslinking agent, the mass ratio of triallyl isocyanurate to trimethylolpropane trimethacrylate is 1:0.25. In the composite organic peroxide, the mass ratio of dicumyl peroxide to bis-tert-butylperoxyisopropylbenzene is 1:0.40, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane accounts for 5% of the total amount of the composite organic peroxide.

[0125] The crosslinking aid masterbatch was prepared at 98℃, with a mixing time of 12 min and a rotation speed of 45 rpm. After cooling the crosslinking aid masterbatch to 65℃, the composite organic peroxide was added in two portions under a negative pressure of -0.05 MPa, with stirring for 12 min after each addition. The low-shear mixing temperature was 90℃, and the mixing time was 10 min. The preheating section temperature of the continuous vulcanization pipeline was 150℃, the main crosslinking section temperature was 188℃, and the post-crosslinking section temperature was 210℃.

[0126] 3. Example 3

[0127] This embodiment is basically the same as Embodiment 1, except that, based on a total volume of 100 parts of cable-grade low-density polyethylene diluted resin and end-group vinyl-enriched low-density polyethylene, the total volume is 75 parts of cable-grade low-density polyethylene diluted resin, 25 parts of end-group vinyl-enriched low-density polyethylene, 1.55 parts of composite organic peroxide, 0.28 parts of reactive crosslinking agent, 0.18 parts of composite antioxidant, and 0.18 parts of anti-scorching regulator.

[0128] The end-vinyl index of the end-vinyl enriched low-density polyethylene is 0.82, the end-vinyl content is 1.05 per 10000°C, the density is 0.923 g / cm³, and the melt mass flow rate is 1.8 g / 10 min.

[0129] In the reactive co-crosslinking agent, the mass ratio of triallyl isocyanurate to trimethylolpropane trimethacrylate is 1:0.75. In the composite organic peroxide, the mass ratio of dicumyl peroxide to bis-tert-butylperoxyisopropylbenzene is 1:0.80, and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane accounts for 18% of the total composite organic peroxide.

[0130] The crosslinking aid masterbatch was prepared at 112℃, with a mixing time of 20 min and a rotation speed of 60 rpm. After cooling the crosslinking aid masterbatch to 78℃, the composite organic peroxide was added in four portions under a negative pressure of -0.07 MPa, with stirring for 8 min after each addition. The low-shear mixing temperature was 100℃, and the mixing time was 15 min. The preheating section temperature of the continuous vulcanization pipeline was 160℃, the main crosslinking section temperature was 200℃, and the post-crosslinking section temperature was 220℃.

[0131] VII. Comparative Example

[0132] 1. Comparative Example 1

[0133] This comparative example uses a conventional direct mixing method to prepare XLPE insulation material. The formulation is as follows: 100 parts cable-grade low-density polyethylene, 1.60 parts dicumyl peroxide, 0.20 parts triallyl isocyanurate, 0.12 parts composite antioxidant, and 0.10 parts anti-scorching modifier. All components are directly mixed and granulated at 100°C. End-group vinyl enrichment of low-density polyethylene is not used, and no crosslinking aid masterbatch or crosslinking efficiency masterbatch is prepared. Cable preparation and degassing conditions are the same as in Example 1.

[0134] 2. Comparative Example 2

[0135] This comparative example uses the same amounts of end-group vinyl-enriched low-density polyethylene, reactive co-crosslinking agent, and composite organic peroxide as in Example 1, but omits the preparation steps of co-crosslinking masterbatch and crosslinking efficiency masterbatch. All components are directly added to a low-shear mixing device at 100°C for mixing and granulation. Cable preparation and degassing conditions are the same as in Example 1.

[0136] 3. Comparative Example 3

[0137] This comparative example uses ordinary cable-grade low-density polyethylene as the masterbatch carrier resin, without using end-group vinyl-enriched low-density polyethylene. The dosages of other reactive co-crosslinking agents, composite organic peroxides, composite antioxidants, and anti-scorching regulators are the same as in Example 1. The masterbatch preparation, low-temperature negative pressure batch addition, and cable manufacturing conditions are the same as in Example 1.

[0138] 4. Comparative Example 4

[0139] This comparative example uses the resin and crosslinking agent system of Example 1, but instead of adding it in 2 to 4 batches when preparing the crosslinking efficiency masterbatch, the composite organic peroxide is added all at once under negative pressure conditions of 70°C and -0.06 MPa, and then discharged after stirring for 30 minutes. Other conditions are the same as in Example 1.

[0140] 5. Comparative Example 5

[0141] This comparative example uses the end-vinyl-enriched low-density polyethylene and reactive co-crosslinking agent system from Example 1, but the composite organic peroxide is only dicumyl peroxide, added in an amount of 1.30 parts. The masterbatch preparation and cable preparation conditions are the same as in Example 1.

[0142] VIII. Test Results

[0143] The crosslinking characteristics test results for each embodiment and comparative example are shown in Table 1. The data are the average values ​​of three parallel tests.

[0144] Table 1. Test results of crosslinking characteristics of insulation materials

[0145]

[0146] As can be seen from Table 1, Examples 1-3 The duration is 7.8–9.4 minutes. The values ​​ranged from 0.221 to 0.233; for comparative examples 1 to 5... The duration is 9.8–11.4 min. The values ​​ranged from 0.135 to 0.182. Under the same test conditions, the torque growth and torque increment per unit amount of peroxide in the crosslinking curves of Examples 1-3 differed from those of the comparative example.

[0147] The gel content, thermal elongation and residual peroxide test results of the XLPE insulation layer 3 prepared in each embodiment and comparative example after degassing are shown in Table 2.

[0148] Table 2. Test results of crosslinking state of XLPE insulation layer

[0149]

[0150] As shown in Table 2, the gel content of Examples 1-3 was not less than 82%, the thermal elongation was not greater than 60%, and the residual peroxide content was not greater than 0.18%. Although Comparative Example 1 used a higher amount of dicumyl peroxide, its thermal elongation and residual peroxide content were higher than those of Example 1. Comparative Example 2 shows that, under the same raw material system, without the staged preparation of the crosslinking aid masterbatch and crosslinking efficiency masterbatch, the thermal elongation and residual content differed from those of Example 1. Comparative Example 3 shows that, when using ordinary low-density polyethylene as the masterbatch carrier, the test results differed from those of the example using end-group vinyl-enriched low-density polyethylene as the masterbatch carrier. Comparative Example 4 shows that, when the composite organic peroxide was added all at once, the thermal elongation and residual content differed from those added in batches. Comparative Example 5 shows that, when using single dicumyl peroxide, the crosslinking state test results differed from those of the composite organic peroxide system.

[0151] The mechanical and electrical properties of the XLPE insulation layer 3 prepared in each embodiment and comparative example are shown in Table 3.

[0152] Table 3 Test results of mechanical and electrical properties of XLPE insulation layer

[0153]

[0154] As shown in Table 3, the XLPE insulation layer 3 prepared in Examples 1-3 all fall within the usable range for power cable insulation layers in terms of tensile strength, elongation at break, power frequency breakdown strength, volume resistivity, and dielectric loss factor. Compared with the comparative examples, Examples 1-3 maintained relatively stable test results in terms of power frequency breakdown strength, volume resistivity, and dielectric loss factor.

[0155] In summary, in this embodiment, after the high-crosslinking-efficiency XLPE insulation material is prepared by the above steps using end-group vinyl-enriched low-density polyethylene, reactive co-crosslinking agent, composite organic peroxide, composite antioxidant, and anti-scorching modifier, it can be formed into XLPE insulation layer 3 through three-layer co-extrusion and continuous vulcanization. In Examples 1-3, the co-crosslinking masterbatch is first prepared at 90-115°C, and the composite organic peroxide is added in batches at 60-80°C under inert atmosphere and negative pressure, and then mixed with cable-grade low-density polyethylene diluted resin under low shear. This process flow differs from the direct mixing, ordinary carrier resin, one-time addition of composite organic peroxide, or single peroxide system in the comparative examples.

[0156] Test results show that the gel content, thermal elongation, peroxide residue, mechanical properties, and electrical properties of the XLPE insulation layer 3 obtained in Examples 1-3 all meet the test requirements set in this embodiment. The comparative results are used to illustrate the influence of each key process step or raw material selection on crosslinking characteristics and insulation layer performance.

[0157] The foregoing description of embodiments of the present invention, through which those skilled in the art are able to implement or use the present invention, will be readily apparent to those skilled in the art. Various modifications to these embodiments will be readily apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novelty disclosed herein.

Claims

1. A power cable with high cross-linking efficiency XLPE insulation, characterized in that, It includes a conductor and a conductor shielding layer, an XLPE insulation layer, an insulating shielding layer, a metal shielding layer, and an outer sheath covering the outside of the conductor; The XLPE insulation layer is formed by three-layer co-extrusion and continuous vulcanization cross-linking of high cross-linking efficiency XLPE insulation material; The raw material system for preparing the high crosslinking efficiency XLPE insulation material includes cable-grade low-density polyethylene diluted resin, end-group vinyl-enriched low-density polyethylene, reactive crosslinking agent, composite organic peroxide, composite antioxidant, and scorch prevention modifier; The preparation process of the high crosslinking efficiency XLPE insulation material includes the following steps: T1. End-group vinyl-enriched low-density polyethylene, reactive co-crosslinking agent and first part of composite antioxidant are added to a closed mixing equipment and melt-dispersed at 90-115°C to obtain co-crosslinking masterbatch. T2. Cool the crosslinking aid masterbatch to 60-80°C, and add the composite organic peroxide in 2-4 portions under an inert atmosphere and a negative pressure of -0.03 to -0.08 MPa. Stir for 5-20 minutes after each addition under the negative pressure before adding the next portion to obtain the crosslinking efficiency masterbatch. T3. The crosslinking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C to obtain the high crosslinking efficiency XLPE insulation material.

2. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, Based on 100 parts of the total amount of the cable-grade low-density polyethylene diluted resin and the end-group vinyl-enriched low-density polyethylene, the high crosslinking efficiency XLPE insulation material comprises the following components: 75-88 parts of cable-grade low-density polyethylene diluted resin; 12-25 parts of end-vinyl-enriched low-density polyethylene; 1.05–1.55 parts of composite organic peroxide; 0.10–0.28 parts of reactive crosslinking agent; 0.06–0.18 parts of composite antioxidant; 0.05–0.18 parts of scorch prevention regulator.

3. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, The end-terminated vinyl-enriched low-density polyethylene has an end-terminated vinyl index of 0.45–0.85, an end-terminated vinyl content of 0.35–1.20 ions / 10000C, a density of 0.918–0.925 g / cm³, a melt flow rate of 1.5–3.0 g / 10 min, a total metal ion impurity content of no more than 5 ppm, and an ash content of no more than 50 ppm.

4. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, The reactive co-crosslinking agent includes triallyl isocyanurate and trimethylolpropane trimethacrylate, with a mass ratio of 1:0.20 to 0.

80. In step T1, the reactive crosslinking agent is added to the closed mixing equipment in 2 to 3 portions, and after each addition, it is melt-dispersed at 90 to 115°C for 3 to 8 minutes. The first part of the composite antioxidant is added after the end-group vinyl-enriched low-density polyethylene begins to melt, and is added before the first addition of the reactive co-crosslinking agent.

5. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, The composite organic peroxide includes dicumyl peroxide, bis-tert-butylperoxyisopropylbenzene and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane; The mass ratio of dicumyl peroxide to bis(tert-butylperoxide) is 1:0.35 to 0.

85. 2,5-Dimethyl-2,5-di-tert-butylperoxyhexane accounts for 5-20% of the total amount of complex organic peroxides.

6. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, When preparing the crosslinking aid masterbatch, the rotation speed of the closed mixing equipment is 30-80 rpm, and the melt dispersion time is 8-25 min; After the crosslinking masterbatch is cooled to 60-80°C, it is first purged under an inert atmosphere for 3-10 minutes before adding the composite organic peroxide, and then the pressure is reduced to -0.03 to -0.08 MPa. When the composite organic peroxide is added in 2 to 4 portions, the temperature fluctuation between two adjacent additions shall not exceed 5°C.

7. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, The crosslinking efficiency masterbatch has a particle size of 0.5–3.0 mm; When the crosslinking efficiency masterbatch is mixed with cable-grade low-density polyethylene diluted resin under low shear, the mixing temperature is 85-105℃, the rotation speed of the mixing equipment is 20-60rpm, and the mixing time is 5-20min. After low-shear mixing, the material is extruded, granulated, cooled at low temperature, and sieved to obtain high cross-linking efficiency XLPE insulation particles. The outlet temperature of the low-temperature air cooling is 15-30℃, and the sieving process retains particles with a particle size of 2-5mm.

8. The high cross-linking efficiency XLPE insulation power cable according to claim 1, characterized in that, The composite antioxidant is composed of a hindered phenolic antioxidant with a melting point of not less than 120°C and a thioester or phosphite auxiliary antioxidant with a melting point of less than 115°C, with a mass ratio of 1:0.25 to 0.

70. The scorching inhibitor is α-methylstyrene dimer, p-benzoquinone scorching inhibitor, or a combination thereof; The XLPE insulation layer, after degassing, has a gel content of not less than 82%, a thermal elongation of not more than 60% under conditions of 200℃ and 0.2MPa, and a residual content of composite organic peroxide not more than 0.18%.

9. A method for preparing a high cross-linking efficiency XLPE insulation power cable as described in any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Weigh out the following according to the formula: end-group vinyl enriched low-density polyethylene, reactive crosslinking agent, composite organic peroxide, composite antioxidant, anti-scorching agent and cable-grade low-density polyethylene diluted resin. S2. End-group vinyl-enriched low-density polyethylene, reactive crosslinking agent and first part of composite antioxidant are added to a closed mixing equipment and melt-mixed in a closed environment at 90-115°C to obtain crosslinking masterbatch. S3. Cool the crosslinking aid masterbatch to 60-80°C, and add the composite organic peroxide in 2-4 portions under an inert atmosphere and a negative pressure of -0.03 to -0.08 MPa. Stir for 5-20 minutes after each addition under the negative pressure to obtain the crosslinking efficiency masterbatch. S4. The cross-linking efficiency masterbatch, cable-grade low-density polyethylene diluted resin, the second part of the composite antioxidant and anti-scorching modifier are mixed under low shear at a temperature not exceeding 105°C and granulated to obtain high cross-linking efficiency XLPE insulation material. S5. The conductor shielding material, high cross-linking efficiency XLPE insulation material and insulation shielding material are co-extruded onto the outside of the conductor through a three-layer co-extrusion die head to form a conductor shielding layer, a cross-linking insulation layer and an insulation shielding layer. S6. The co-extruded cable core is fed into a continuous vulcanization pipeline to cross-link the insulation layer to be cross-linked to form an XLPE insulation layer. S7. Cool, degas, wrap with a metal shielding layer and extrude an outer sheath after cross-linking of the cable core to obtain the high cross-linking efficiency XLPE insulation power cable.

10. The preparation method according to claim 9, characterized in that, In step S6, the continuous vulcanizing pipeline is sequentially provided with a preheating section, a main cross-linking section, and a post-cross-linking section along the direction of travel of the co-extruded cable core; The temperature of the preheating section is 145-165℃, the temperature of the main crosslinking section is 180-205℃, and the temperature of the post-crosslinking section is 205-225℃; and / or, in step S7, the degassing is carried out at 60-80℃ for 48-96 hours.

Citation Information

Patent Citations

  • Peroxide cross-linked polyethylene cable material for insulating layer and manufacturing method of peroxide cross-linked polyethylene cable material

    CN115819872A